Efficacy of nursing interventions based on the enhanced recovery after surgery (ERAS) in patients with lumbar disc herniation - Huan Yang; Qian Yang; MingShan Pu; Chao Liao (Scientific Reports)
Abstract Enhanced Recovery After Surgery (ERAS) principles have been increasingly applied in various surgical disciplines to optimize patient outcomes and reduce recovery times. However, evidence regarding the application of ERAS-based nursing interventions in lumbar disc herniation (LDH) management remains limited. This study aimed to evaluate the efficacy of ERAS-based nursing interventions in improving recovery outcomes for patients undergoing surgical treatment for LDH. A total of 345 patients diagnosed with LDH and undergoing surgical treatment between February 2022 and February 2023 were retrospectively analyzed. Patients were divided into two groups: 174 received ERAS-based nursing interventions, while 171 received standard care. ERAS interventions included preoperative education, multimodal pain management, early mobilization, and psychological support. Clinical outcomes, including postoperative pain measured by the Visual Analog Scale (VAS), length of hospital stay (LOS), complication rates, and patient satisfaction, were assessed. Recovery milestones, such as time to ambulation and return to daily activities, were also analyzed.The ERAS group demonstrated significantly better outcomes compared to the standard care group. Postoperative VAS scores were lower in the ERAS group at 24 h (3.7 ± 1.2 vs. 5.1 ± 1.4, P < 0.001) and 48 h (2.8 ± 0.9 vs. 4.3 ± 1.2, P < 0.001). The ERAS group also had a shorter LOS (5.3 ± 1.7 days vs. 7.1 ± 2.2 days, P < 0.001), fewer complications (6.9% vs. 12.3%, P = 0.037), and higher patient satisfaction (92.6% vs. 78.9%, P < 0.001). Recovery milestones, including time to ambulation (18.5 ± 4.6 h vs. 30.2 ± 5.9 h, P < 0.001) and return to daily activities (7.4 ± 1.5 days vs. 10.2 ± 2.1 days, P < 0.001), were achieved earlier in the ERAS group. ERAS-based nursing interventions significantly improve recovery outcomes for patients undergoing surgical treatment for lumbar disc herniation. These findings highlight the importance of integrating ERAS principles into perioperative nursing care to enhance patient recovery and satisfaction.